International trade, union wage premia, and welfare in general equilibrium - Udo Kreickemeier; Frode Meland (Center for Economic Studies and ifo Institute (CESifo), 2011)
We study how two distinct forms of globalisation, trade cost reductions and opening up of trade in previously shielded sectors, affect sector-specific wages, employment levels and aggregate welfare in a two-country model of general oligopolistic equilibrium (GOLE) with partly unionised labour markets. We find that both forms of globalisation increase union coverage, and they also lead to a lower union wage premium in shielded sectors. In contrast, the union wage premium in open sectors and aggregate welfare are affected differently by the two types of globalisation. Trade cost reductions in open sectors always lead to higher union wage premia and to lower aggregate welfare, while an increased number of open sectors lowers the union wage premium, and it may also increase welfare.
Keywords: F12; F15; F16; 330; globalisation; unions; non-traded goods; general oligopolistic equilibrium; Nicht-handelbares Gut; Globalisierung; Gewerkschaftlicher Organisationsgrad; Wohlfahrtseffekt; Allgemeines Gleichgewicht; Außenwirtschaftstheorie; Theorie